Peningkatan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Menggunakan Model Pembelajaran Inovatif di Kelas IV SDN 24 Koto Raya Kabupaten Pesisir Selatan - Nelvagia, Nelvagia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education and Character Education in grade IV at SDN 24 Koto Raya, using an innovative learning model. The research was conducted through Classroom Action Research (CAR) consisting of two cycles. The results showed that in the first cycle, the implementation of the innovative learning model still required improvements in classroom management and student motivation. However, in the second cycle, there was a significant improvement in students' learning outcomes, with most students achieving the Minimum Completion Criteria (KKM). The application of the innovative learning model proved to be effective in enhancing student participation and understanding, and can be considered an alternative to improving the quality of Islamic Religious Education at the elementary school level..